A Full-Scale Test by Low-Improvement-Rate Soil in Combination with Crushed-Stone Mat on Peaty Ground - H. Hashimoto; T. Yamanashi; H. Hayashi; M. Yamaki (Deep Foundations Institute, 2015)
"In an experiment on a trial embankment, the deformation mode of the improved ground at the toe of the embankment was compared with the deformation mode of the unimproved ground. This comparison showed that the behavior exhibited by the improved ground was the same as that exhibited by the unimproved ground, despite the low improvement rate (ap = 10%) of the ground improvement. Thus, the improved ground and the unimproved ground were found to be functioning as composite ground. Further, the strain that developed in the geo-textile used for the crushed-stone mat was considerably less than the strain specified by the design strength. As a result, it was found that a crushed-stone mat can serve as a mattress.OVERVIEW OF THE TEST CONSTRUCTIONLow Improvement-Rate Soil in Combination with Crushed-Stone MatIn Hokkaido, approximately 2,000 km2 of the land is peat land, an area almost as large as Tokyo. Such land accounts for 6% of Hokkaido’s plains and 2.4% of its total land area. The peat layer is normally 3 to 5 m thick and underlain by a layer of soft, cohesive soil whose thickness may exceed 20 m. In such a ground, consolidation using cement may generate differential settlement between improved soil as a result of embankment construction or lateral deformation caused by the slipping of unimproved ground. Therefore, the improvement ratio (ap) is designed to be at least 50% by the Manual for Construction on Soft Peaty Ground (CERI, 2011 [1]). Consolidation of ground with a low improvement ratio in combination with crushed stone-mat installation is a measure for soft ground (Figure 1). In this method, soil with a lower Improvement ratio than that of conventional improved soil (e.g., ap=10%) is placed beneath the entire embankment and a “crush stone mat”, a layer of crushed stone (t=0.5 m) enclosed by geo-textile, is then placed between the embankment and the soil."